Meditaciones morales de Descartes: pasión y auto conservación de la vida - Burlando, Giannina (Veritas, 2011)
The hypothesis held in the current study is that Descartes is truly concerned about moral matters; that his moral meditations involve a doctúne on the passions of the soul and a conception of life as well, both of them intrinsically tied up. Thus, my pupose is as follows: first, to show that it is possible to reconstruct crucial aspects of Descartess moral meditations after the analysis of his copus doctúnae: that his moral stand involves a new conception of the passions. Secondly, I shall underline that ethos y pathos are connected in his úews; that this connection is explica in Descartess ideas of practical knowkdge, namely, in the sort of praxis recon as «the exercise ofúrtue», the «úvre heureusement». Thirdly 1 mili approach the question on wherein does cartesian morality lye? ¿Is it a matter of concepts, judgments, character, education, action and practical wisdom, or rather a question of the intúnsic properties of things and human agents, or even a mixture among some of these?